In Search for Boundary Conditions of Reconsolidation: A Failure of Fear Memory Interference - Schroyens, Natalie; Beckers, Tom; Kindt, Merel (Frontiers in Behavioral Neuroscience, 2017)
The presentation of a fear memory cue can result in mere memory retrieval, destabilization of the reactivated memory trace, or the formation of an extinction memory. The interaction between the degree of novelty during reactivation and previous learning conditions is thought to determine the outcome of a reactivation session. This study aimed to evaluate whether contextual novelty can prevent cue-induced destabilization and disruption of a fear memory acquired by non-asymptotic learning. To this end, fear memory was reactivated in a novel context or in the original context of learning, and fear memory reactivation was followed by the administration of propranolol, an amnestic drug. Remarkably, fear memory was not impaired by post-reactivation propranolol administration or extinction training under the usual conditions used in our lab, irrespective of the reactivation context. These unexpected findings are discussed in the light of our current experimental parameters and alleged boundary conditions on memory destabilization.